The Use and Transformation of Formal Decision-Making Criteria: Sentencing Guidelines, Organizational Contexts, and Case Processing Strategies. (31st July 2014) - Ulmer, Jeffery T.; Kramer, John H.
Abstract : Recent sociological research in organizations has emphasized the "filtering" of externally-imposed formal policies and rules through local organizational cultures and strategic interaction processes. This type of generic organizational process assumes special importance for courts and sentencing, subjects of policy-oriented and social problems discourse for over three decades. Eisenstein and associates (1977, 1988; Flemming, Nardulli and Eisenstein 1992) point out that the contexts of local "court communities" and the formal and informal case processing norms of courtroom workgroups are at least as important as formal laws and state-level policies in determining "contours" of criminal justice. Our study focuses on the use and transformation of sentencing guidelines in the interorganizational relations and workgroup case processing strategies in local courts. We draw on the organizational concepts of "embeddedness" (Perrucci 1994) and "properties in use" (Peyrot 1995) of formal decision-making tools to frame our analysis. We present qualitative interview and field data on organizational contexts and case processing strategies from three different-sized county trial courts in Pennsylvania, a state whose courts have operated under sentencing guidelines for over a decade. Among the highlights of the analysis are our findings that DA's offices can use sentencing guidelines as management tools, judges can use them to legitimate their sentencing practices in political disputes, and both prosecutors and defense attorneys use them as important tools of uncertainty reduction in their guilty plea strategies. More generally, we argue that the implimentation of externally imposed formal rules and decision-making criteria depends on local relationships, activities, and informal decision-making criteria.